The shifting identity of a first-year class in Practical Theology: Some tentative reflections on decolonization - Nell, Ian (Stellenbosch Theological Journal, 2024)
I started 2020 with 130 first-year students enrolled for Practical Theology and Missiology at the Faculty of Theology, Stellenbosch University, South Africa. The students represent twenty different denominations, 75 percent of the students are black, coloured, and Indian (BCI) and 25 percent are white. Ten years ago, the same first-year class consisted of thirty students, of whom 95 percent were white and almost all were part of the Reformed tradition. The shifting identity of the class over a decade inevitably led me to reflect deeply on what I teach them (curriculum) and how I facilitate the learning process (pedagogy). I also had to pay close attention to decolonization and contextualization because of the #feesmustfall-movement. The basic research question of this contribution is therefore: How does one reflect on the shifting identity of a first-year class and how does one decolonize a first-year module in Practical Theology and Missiology in South Africa? In order to answer the research question, the article takes the following steps: first, aspects of the changed context and shifting identity will be discussed and second, attention will be given to what is meant by decolonization, with specific reference to the curriculum. Third, the focus will be on a proposed curriculum that uses a theo-dramatic approach in conversation with the movie Son of Man. Fourth, I reflect on the learning process (pedagogy) and how it also contributed to a shift in my own identity.